Stroke mimic: an interesting case of repetitive conversion disorder. (30th November 2012) - Segal, Jonathan; Lam, Alison; Dubrey, Simon William; Vasileiadis, Evangelos
Abstract : Stroke mimics can account for up to 5% of all acute stroke presentations.They are more frequent in those under 50 years of age, with some estimates of prevalence as high as 21% of acute stroke presentations in this age group. We describe a case of repetitive stroke mimic episodes, the recognised associated precipitants, diagnostic clues and management.